2018
DOI: 10.4236/ojemd.2018.81003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pheochromocytoma in Dakar: Diagnostic and Therapeutic Advances throughout 16 Cases

Abstract: Introduction: Management of pheochromocytoma faces different challenges leading to misdiagnosis and therapeutic delay in developing countries. The aim of our study was to evaluate the diagnostic and therapeutic features as well as the evolution of our management strategies in hospital setting in recent years in Dakar. Patients and Method: We carried out a retrospective study over 12 years (January 2005 to June 2017), in 4 hospitals in Dakar. We only included patients with established diagnosis of pheochromocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…All major postoperative adverse events occurred in the patients undergoing open resection, with the exception of one laparoscopic case that had a relook for suspected intra‐abdominal sepsis; the relook laparoscopy was non‐therapeutic and the patient recovered uneventfully. Perioperative mortality for PPGL is uncommon, with the 1% found in this series in keeping with 0–6% found elsewhere [8–10, 12, 14, 15, 17, 21]. The patient had a symptomatic 7 cm tumor on the left side which was found to completely encase the celiac trunk.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…All major postoperative adverse events occurred in the patients undergoing open resection, with the exception of one laparoscopic case that had a relook for suspected intra‐abdominal sepsis; the relook laparoscopy was non‐therapeutic and the patient recovered uneventfully. Perioperative mortality for PPGL is uncommon, with the 1% found in this series in keeping with 0–6% found elsewhere [8–10, 12, 14, 15, 17, 21]. The patient had a symptomatic 7 cm tumor on the left side which was found to completely encase the celiac trunk.…”
Section: Discussionsupporting
confidence: 84%
“…Although well described in developed nations, there is a paucity of data on the presentation and surgical management of PPGL in developing world contexts, particularly in Sub-Saharan Africa [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This unusual clinical presentation could be attributed to the large size of AT in our patients, 20 had AT of between 4 and 10 cm, and 10 had tumours larger than 10 cm. The large size of the tumours could also explain the performance of abdominal ultrasound in our study [13], which was performed in 15 patients (42%) and consistently revealed an adrenal mass. CT is often the preferred initial imaging approach for adult adrenal evaluation due to its widespread availability, reproducibility, good temporal resolution, and superior spatial resolution compared with MR imaging.…”
Section: Discussionmentioning
confidence: 64%